Similarities and Differences Between Eye and Mouse Dynamics During Web Pages Exploration - Milisavljevic, Alexandre; Abate, Fabrice; Le Bras, Thomas; Gosselin, Bernard; Mancas, Matei; Doré-Mazars, Karine (Frontiers in Psychology, 2021)
The study of eye movements is a common way to non-invasively understand and analyse human behaviour. However, eye-tracking techniques are very hard to scale, and require expensive equipment and extensive expertise. In the context of web browsing, these issues could be overcome by studying the link between the eye and the computer mouse. Here, we propose new analysis methods, and a more advanced characterisation of this link. To this end, we recorded the eye, mouse and scroll movements of 151 participants exploring 18 dynamic web pages while performing free viewing and visual search tasks for 20 seconds. The data revealed significant differences of eye, mouse and scroll parameters over time which stabilise at the end of exploration. This suggests the existence of a task-independent relationship between eye, mouse and scroll parameters which are characterised by two distinct patterns: one common pat- tern for movement parameters and a second for dwelling/fixation parameters. Within these patterns, mouse and eye movements remained consistent with each other, while the scrolling behaved the opposite way.